Development of E-Booklet Learning Media in the Topic of Environmental Pollution for Junior High School Students - Avrina Erawati; Laily Yunita Susanti (Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Jember, 2022)
Environmental Pollution Material is one of the science learning materials with conceptual and factual characteristics. In this regard, the Astra Nawa Superior Middle School explained that the environment was polluted so that observations could be made. There are obstacles in learning science at Astra Nawa Superior Middle School, namely, the lack use of variative learning media. The aims of this study were 1) to describe the validity of e-booklet learning media on Environmental Pollution material for junior high school students; 2) To describe student responses toward e-booklet learning media. The type of study is Research and Development with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The validation of the e-booklet learning media was from material experts and media experts consisting of science lecturers and teachers. Small-scale student response test, namely 6 students in a large-scale response test of 32 students. Based on the results of development research, it can be concluded that the average percentage of the validation test for material experts is 80.66%, media experts are 94.28% and science teachers are 95.29% with a very valid category. The results of the small-scale trial response obtained 85.47% and the large-scale trial obtained 86.56% with a very valid category, so that e-booklet learning media can be used in the learning process. According to the findings, it can be concluded that e-booklet learning media can be used in the learning process.